CTNI-23. PRELIMINARY SAFETY AND PHARMACOKINETICS DATA FOR A PHASE 1B TRIAL OF TELAGLENASTAT IN COMBINATION WITH RADIATION THERAPY AND TEMOZOLOMIDE IN PATIENTS WITH IDH-MUTANT GRADE 2/3 ASTROCYTOMA (NCI-10218). (14th November 2022) - Kizilbash, Sani; Piccioni, David; Sahebjam, Solmaz; Villano, John; Jaeckle, Kurt; Welch, Mary; Kong, Xiao-Tang; Holdhoff, Matthias; Lammers, Anita; Remick, Adam; Reid, Joel; Allred, Jacob; et al.
Abstract: IDH mutant gliomas depend on glutaminase for glutamate/glutathione generation from glutamine because R-2-hydroxyglutarate inhibits branched chain amino acid transaminase mediated glutamate biosynthesis. Telaglenastat (CB-839 HCl) is a potent glutaminase-1 specific inhibitor which depletes tumor glutamate in orthotopic IDH mutant glioma PDX models and extends survival in these orthotopic models when added to radiation/temozolomide. NCI-10218 (NCT03528642) is a phase I clinical trial investigating the safety and tolerability of telaglenastat administered orally concurrently with standard doses of radiation (50.4 Gy, grade 2; 59.4 Gy, grade 3) and temozolomide (75 mg/m2 orally daily) in patients (age 16+) with previously untreated IDH mutant grade 2/3 astrocytoma. Telaglenastat dose was escalated in cohorts (400-800 mg twice daily) based on a standard 3 + 3 design to determine the recommended phase 2 dose (RP2D). Toxicities were graded per CTCAE v5.0. An expansion cohort additionally incorporated a seven-day run-in of telaglenastat monotherapy at RP2D prior to radiation to evaluate the pharmacodynamic impact of telaglenastat on plasma and tumor metabolites. 23 patients with IDH mutant astrocytoma (WHO grade 2, n = 5; WHO grade 3, n = 18) were accrued between December 2018 and January 2022 (Dose Escalation: 16; Dose Expansion: 7). Median age was 32 years (range 23-69 years). 61% were male and 70% were ECOG 0. No dose-limiting toxicities were observed. Grade 3/4 adverse events (independent of attribution) included: lymphopenia (3), neutropenia (2), leukocytosis (2), alanine transaminase elevation (2), thrombocytopenia (1), leukopenia (1), maculopapular rash (1), hyperglycemia (1), hyponatremia (1). The RP2D of concurrent telaglenastat was defined as 800 mg twice daily. Following peak absorption on Day 15 at RP2D, the mean (%CV) terminal elimination half-life in the plasma was 4.2 (53.5%) hours (range 2.1-7.1 hours). The Cmax, Tmax, oral clearance, and AUC were 1496 ng/mL, 4.0 hr, 93.6 L/hr/m2, and 7430 ng/mL*hr, respectively.